The impact of in-work benefits on employment and poverty - Dieter Vandelannoote; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This article studies the impact of design characteristics of in-work benefits on employment and poverty in an international comparative setting, taking account of both first and second order labour supply effects. We use the micro-simulation model EUROMOD, which has been enriched with a discrete labour supply model. The analysis is performed for four EU-member states: Belgium, Italy, Poland and Sweden. The results show that design characteristics matter substantially, though the specific effects differ in magnitude across countries, indicating there is no one-size-fits-all solution. Throughout the analysis, numerous trade-offs are uncovered: not only between employment and poverty goals, but also within employment incentives itself (extensive vs. intensive margin). Taking account of behavioural reactions attenuates the impact on poverty outcomes, signalling the importance of bringing these effects into the empirical analysis.
Keywords: D13; D31; J22; 330; in-work benefits; design characteristics; labour supply; at risk of poverty